Tahzeeb-e-Niswan and Female Tareekh Goi - Imran Tabassum (بازیافت)
Tareekhgoi (chronogram), a revered art among classical Urdu poets, ingeniously encoded dates within poetic verses using Arabic numeral values of letters. Historically, when formal record-keeping was scarce, these chronograms served as mnemonic devices for significant events. Mastery of Tareekhgoi demanded poetic finesse and numerological expertise, leading to the misconception that it was a male-dominated craft. However, with the advent of colonial-era education, women poets defied this notion. Tehzeeb-e-Niswan, a pioneering women’s magazine, became a platform for female voices to excel in Tareekhgoi, publishing hundreds of verses on diverse occasions—from births to cultural milestones. These contributions dismantled gender biases and cemented women’s place in Urdu literary history. This groundbreaking study is the first to analyze the volume, themes, and artistic merit of chronograms published in Tehzeeb-e-Niswan, revealing their expressive range and socio-cultural significance. By documenting this overlooked legacy, the research paves the way for future scholarly exploration of gendered literary traditions in Urdu.“Tehzeeb-e-Niswan” was a magazine, which was dedicated to women's writings and encouraged new female writers or poets. Empowered by this magazine, women started getting their standing in poetry and literature and there came a time when the women who wrote in the magazine “Tehzeeb-e-Niswan” had become renowned writers and poets of their time. These same women also demonstrated the art of Tarikhgui on the pages of “Tehzeeb-e-Niswan” and wrote hundreds of verses, proving wrong the idea that only male poets could master this art. The article under consideration has examined how many historical verses were published in Tehzeeb Niswan and what was their artistic status. It has also been examined on what kind of different occasions the poets recited verses and how much diversity there was in their expression. This is the first research work on this topic in Urdu, which can open avenues for further research in the future.